INCIDENTI STRADALI PROVOCATI DA ANIMALI: PROFILI NORMATIVI, RESPONSABILITA’ E LINEE GUIDA GESTIONALI (Rassegna di Diritto, Legislazione e Medicina Legale Veterinaria, 2017)
Nowadays, car accidents caused by animals, especially wildlife animals, are increasing. In this article the Authors analyze the regulatory aspects concerning the responsibility for damage caused by accidents involving animals. The most recent provisions of the Highway Code on aid to the animals involved in accidents are discussed. A protocol to effectively manage individual situations is proposed.